Kitui county leverages ADD-IT app for JICA-backed nutrition initiative and conducts dietary assessment across 322 households - Morimoto, Yasuyuki; Maundu, Patrick; Irie, Kenji; Kenjiro, Ban; Takemura, Tomo; Minakuchi, Kosuke (2025)
In January 2024, the Kitui County government of Kenya, supported by IFNA, AUDA-NEPAD, and JICA, adopted the Semi-Quantitative Food Frequency Questionnaire (SFFQ)—a key feature of the Alliance's ADD-IT app. The pilot project aims to improve the nutritional status of children under two years old and their mothers. The dietary assessment was conducted across 322 households in two communities. County officials and 20 community health promoters (CHPs) identified dietary gaps to raise awareness of individualized challenges and guide evidence-based improved dietary practices.